Pengaruh Pembelajaran Matematika Melalui Media Audiovisual Terhadap Kemampuan Literasi dan Numerasi Siswa Kelas X SMK Nurul Jadid - Ivatun Mardiyah; Moh Syadidul Itqon (CV Edujavare Publishing, 2026)
Mathematics learning often faces difficulties in conveying complex concepts that are difficult for students to understand. To make the material easier to understand, appropriate learning tools are needed. One effective tool is audiovisual media. SMK Nurul Jadid is a vocational high school committed to providing high-quality vocational education with modern facilities and experienced teachers, so that the learning environment supports the implementation of innovative learning methods such as the use of audiovisual media in mathematics subjects. This study aims to see how the use of audiovisual media affects the mathematics learning process in class X SMK Nurul Jadid. The method used is a Systematic Literature Review (SLR). The results of the study show that audiovisual media is very effective in mathematics learning. The use of this media can attract students' attention, increase learning motivation, and improve students' literacy and numeracy skills.